Thomas Aquinas' trinitarian theology: a study in theological method - Smith, Timothy L. (Catholic Univ. of America Press, 2003)
Thomas Aquinas's work on the Trinity in his "Summa Theologiae" has since the 1900s been seen, along with Augustine's "De Trinitate", as representative of a Latin trinitarian tradition. This tradition is assumed to begin with the one God, the one divine essence as a whole. Only afterwards does it see God as three in persons. Philosophical conerns - rather than the revelation of God in Christ - are assumed to be the basis for the discussion. According to many modern theologians the immanent life of God in this tradition is thereby separated from the rest of Christian faith and consequently, has no relevance for the believer. This book examines Thomas's trinitarian theology in light of this criticism. Thomas's account of the Trinity of Persons and the coherence of language about those Persons is not a rational demonstration but an expression of faith seeking understanding. The crucial foundation for this is Thomas's theory of divine naming. The later chapters examine possible influences upon Thomas. Smith concludes that although Thomas is best understood when read in light of his own intellectual context, one cannot assume that every influence is positive.